(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In the article, analytical dependencies are obtained, which allow to determine the rational values of the parameters of the working organ (alignment angles to the horizon and sealing parts, the length of the working surface of the sealing part, the height of the working member and the vertical load on it), and the racists are shown to be obtained from them